Arthur's reading race - Brown, Marc Tolon (New York : Random House, 1996)
Arthur doesn't believe that his little sister can really read, so he challenges her to prove it.
"Step into reading sticker books."
140
140
Accelerated Reader AR
Keywords: Reading -- Fiction; Brothers and sisters -- Fiction; Aardvark -- Fiction